Sinergitas Stakeholders dalam Pengelolaan Sampah di Kota Metro - Maulidya, Ade (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Lampung, 2020)
The purpose of this article is to describe the synergy of stakeholders in waste management in Metro Cities. This type of research is descriptive with a qualitative approach. The results of this study indicate that: (1) waste management in metro city involves five elements, namely: government, civil society, business actors, academics and the media. Cooperation between stakeholders has been going well, but not all stakeholders involved in waste management carry out their roles optimally; (2) communication and coordination is still lacking, as indicated by several complaints from the public; (3) lack of public awareness of waste management in Metro City. Research recommendation: in increasing synergy, it is necessary to evaluate the cooperation between stakeholders. It is hoped that DLH can improve communication and coordination of waste management. Increase waste management activities and increase activities through online media which are expected to increase public awareness of the importance of managing waste.